Fear Conditioning and Extinction in Twins Discordant for Combat Exposure and PTSD. - Offringa, Reid. (2017)
Abstract: Posttraumatic stress disorder (PTSD) is an anxiety disorder that develops in a minority of people after exposure to a traumatic event. For these people, previously non-emotional stimuli become associated with the traumatic event, causing a significant amount of psychological distress. For instance, a veteran who served on a swift boat may find that fishing boats evoke powerful emotional reactions, due to an association with his combat experience. Because PTSD involves emotional associations with an aversive stimulus (like combat exposure), some researchers have chosen to frame PTSD in the context of fear conditioning and extinction. "Conditioning" refers to the process of associating an aversive stimulus with a neutral stimulus, which causes the neutral stimulus to acquire aversive properties. This closely parallels the etiology of PTSD, where neutral stimuli (like boats) can become associated with a traumatic event (like exposure to combat), and may have the potential to illuminate how PTSD develops. "Extinction" refers to the process of disassociating a previously neutral stimulus from the aversive properties that it has acquired. This closely parallels the therapeutic technique of exposure therapy, which has been successfully used to reduce or alleviate PTSD symptoms. The present paper will first cover a brief history of fear conditioning research and explain the theory behind fear conditioning as it pertains to PTSD. Afterward, this paper will compare fear conditioning and extinction measures in PTSD and control groups, exploring each stage of the paradigm separately: acquisition of the fear memory, extinction of the fear memory, and recall of the extinction memory. Finally, this paper will describe an experiment aimed at dissociating familial vulnerability factors from acquired PTSD characteristics, related to fear conditioning and extinction. We report that a reduced differential fear response is a familial vulnerability factor for PTSD, while reduced extinction recall is an acquired PTSD characteristic.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Psychology.; Advisor: Lisa Shin.; Committee: Heather Urry, Mohammed Milad, and Joseph DeBold.; Keywords: Psychology, and Psychobiology.